System analysis and modeling: about models 6th International workshop, SAM 2010, Oslo, Norway, October 4-5, 2010, revised selected papers - Herrmann, Peter (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 6th International Workshop on Systems Analysis and Modeling, SAM 2010, held in collocation with MODELS 2010 in Oslo, Norway in October 2010. The 15 revised full papers presented went through two rounds of reviewing and improvement. The papers are organized in topical sections on modularity, composition, choreography, application of SDL and UML; SDL language profiles; code generation and model transformations; verification and analysis; and user requirements notification.